2012
DOI: 10.1586/ern.11.197
|View full text |Cite
|
Sign up to set email alerts
|

A new sublingual formulation of zolpidem for the treatment of sleep-onset insomnia

Abstract: Insomnia is a very frequent complaint that periodically or permanently affects up to 60% of the general population. Valuable therapeutic options rely on pharmacological and nonpharmacological management of insomnia complaints. Zolpidem is one of the most popular hypnotic drugs used to treat insomnia. The drug was synthesized by Synthélabo Recherche in the early 1980s and has proved to be a suitable and well-tolerated drug, especially with regard to efficacy in sleep initiation. The present review focuses on an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 103 publications
0
4
0
Order By: Relevance
“…Thereafter, the fitted parameter values were transferred to PK‐Sim, and the specific intestinal permeability was fitted to pharmacokinetic data in the fasted state from multiple clinical studies 27,28,31–33 . Another independent set of clinical data not used during parameter optimization was thereafter used to evaluate the adult PBPK model 34–45 …”
Section: Methodsmentioning
confidence: 99%
“…Thereafter, the fitted parameter values were transferred to PK‐Sim, and the specific intestinal permeability was fitted to pharmacokinetic data in the fasted state from multiple clinical studies 27,28,31–33 . Another independent set of clinical data not used during parameter optimization was thereafter used to evaluate the adult PBPK model 34–45 …”
Section: Methodsmentioning
confidence: 99%
“…Thus, fast-acting low-dose zolpidem is associated with a rapid onset of short-term (four hours) sedation. This formulation does not appear to accumulate in the plasma, even after long-term administration [23]. …”
Section: Pharmacokinetics Of Sublingual Formulationsmentioning
confidence: 99%
“…1 It is characterized by one or more of the following subjective complaints: a) a sleep onset latency of over 30 min, b) nightly sleep duration of less than 6 h, and/or c) waking too early and being unable to return to sleep (also referred to as unrefreshed sleep). 2 Studies conducted in the general population indicate that adults experience more of these symptoms, while the National Sleep Foundation's Sleep in America Poll 2005 found that more than 50% of Americans were Declaration of Interests: The authors certify that they have no commercial or associative interest that represents a conflict of interest in connection with the manuscript.…”
Section: Introductionmentioning
confidence: 99%